2014
DOI: 10.1007/s11096-014-9961-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the risk factors for linezolid-induced thrombocytopenia in adult Japanese patients

Abstract: Receiving linezolid therapy for ≥14 days and a low creatinine clearance rate were suggested to be risk factors for linezolid-induced thrombocytopenia. The platelet counts of patients with these risk factors should be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 14 publications
7
74
4
Order By: Relevance
“…When patients were categorized into 3 groups using 2 cut-off values (17, 22 kg/mg/day) of dosage amount, the prevalence of thrombocytopenia in each groups was not significantly different (Reduction rate of >25%; <17 mg/kg/day (69.2%), 17 -22 mg/kg/day (69.2%), >22 mg/kg/day (75.9%), p = 0.90: Reduction rate of >50%; <17 mg/kg/day (38.5%), 17 -22 mg/kg/day (50.0%), >22 mg/kg/day (44.8%), p = 0.84). While prolonged treatment duration for more than 14 days has been reported as risk factors for linezolid-induced thrombocytopenia [7], the proportion of patients with thrombocytopenia did not show significant difference between patients with linezolid therapy for more than 14 days and patients with linezolid therapy for less than 13 days in our study (40.0% vs 45.3%, p = 0.87, Table 2). There were not significant differences in the body size descriptors between linezolid therapy for more than 14 days and for less than 13 days (Table 2).…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…When patients were categorized into 3 groups using 2 cut-off values (17, 22 kg/mg/day) of dosage amount, the prevalence of thrombocytopenia in each groups was not significantly different (Reduction rate of >25%; <17 mg/kg/day (69.2%), 17 -22 mg/kg/day (69.2%), >22 mg/kg/day (75.9%), p = 0.90: Reduction rate of >50%; <17 mg/kg/day (38.5%), 17 -22 mg/kg/day (50.0%), >22 mg/kg/day (44.8%), p = 0.84). While prolonged treatment duration for more than 14 days has been reported as risk factors for linezolid-induced thrombocytopenia [7], the proportion of patients with thrombocytopenia did not show significant difference between patients with linezolid therapy for more than 14 days and patients with linezolid therapy for less than 13 days in our study (40.0% vs 45.3%, p = 0.87, Table 2). There were not significant differences in the body size descriptors between linezolid therapy for more than 14 days and for less than 13 days (Table 2).…”
Section: Resultscontrasting
confidence: 77%
“…Prolonged treatment duration [7], renal insufficiencies [8], chronic liver disease [8] and lower body weight [2] have been reported as possible risk factors for linezolid-induced thrombocytopenia. Additionally, Natsumoto et al showed that both higher daily dose (mg/kg/day) (prevalence of thrombocytopenia; <17 mg/kg/day (17%), 17 -22 mg/kg/day (34%), 22 -27 mg/kg/day (48%), >27 mg/kg/day (72%)) and elevated serum creatinine were significant risk factors for linezolid-induced thrombocytopenia in non-hemodialysis patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reports soon emerged of increased thrombocytopenia in this population with multiple-dose administration (10,11). This finding has since been replicated in multiple observational studies, most of which have been conducted in Asian populations (12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 86%
“…While establishing appropriate measures to improve clinical outcomes for the patients are essential tasks for clinicians, published studies reporting the incidence and predictive factors for linezolid‐induced thrombocytopenia had been insufficient and often limited due to the variabilities of the study design and patient population. Most studies included patients with haemato‐oncologic diseases without distinguishing subgroups or disease severity as the presence of haemato‐oncologic diseases or variable status of myelosuppression can be a significant confounder in the evaluation of thrombocytopenia. Moreover, a number of studies included patients with a baseline platelet count of <100 × 10 3 /mm 3 in their populations, indicating that these patients already had thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%